The Effect of Job Training, Performance Assessment, and Work Motivation on the Performance of Production Division Employees at PT Rinnai Indonesia (Case Study of the Gas Valve Division) - Arnas Nur Rohimah; Miyv Fayzhall; Bonar Bangun Jeppri Napitupulu; Masduki Asbari (Faculty of Science and Technology University of Pramita Indonesia, 2022)
Rinnai Indonesia is an industrial company engaged in manufacturing that produces various kinds of household needs. The purpose of this study was to determine the effect of job training, performance appraisal, and work motivation on the performance of production employees at PT. Rinnai Indonesia. With job training research variables as X1, performance appraisal as X2, work motivation as X3, and employee performance as Y. The method used is a quantitative method with a sampling technique using the slovin method with sample members to examine as many as 87 people. Data collection using a Likert scale. The analysis technique uses statistical analysis with instrument testing, classical assumptions, correlation, determination, regression, and hypothesis testing. The results of the research on the job training, performance appraisal, and work motivation variables have a positive and significant effect on employee performance with a regression equation value of Y= 6.175 + 0.500X1 + 0.259X2 + 0.083X3 and a correlation coefficient value of 0.926 or has a very strong relationship with a determination value of 86, 9%. The hypothesis test obtained significant 0.000 <0.05. So simultaneously job training, performance appraisal, and work motivation have a positive and significant influence on the performance of employees in the production department at PT. Rinnai Indonesia, partially job training has a positive and significant impact on the performance of employees in the production department at PT. Rinnai Indonesia, partial performance appraisal has a positive and significant impact on the performance of employees in the production department at PT. Rinnai Indonesia and partially work motivation have a positive and significant influence partially on the performance of employees in the production department at PT. Rinnai Indonesia